The Analyzing of Jane Eyre by Charlotte Bronte - Mohammad Thoriq (LINGUAMEDIA Journal, 2020)
This research entitled “The Analyzing of Jane Eyre by Charlotte Bronte”. It will analyze the novel based on five aspects; plot, theme, setting, character and characterization, and point of view. Plot is story which contains the sequence of events was only connected is cause and effect, one event is cause the other event. After analyzing the story, we can know that the author uses the forward plot. What the author wants to convey is the central idea of the story and is known as the ‘theme’. This story has a theme about “The struggle of love in the differentials of social”. Then setting is when and where a story happens. Setting can be setting of time and setting of place. Character and characteristic take into consideration: What the character says; What he does, his action; What others says about him; and What others do (their action may help to indicate what the character could do or not). Point of view is the viewpoint of the story. Writers use first person point of view or third person point of view. In first person point of view, the main character tells the story. In third person point of view, the narrator tells the story. But after analyze this story; we can know that point of view is first person. The “I” is the character who tells the story. The author is often protagonist. In this research, the writer used design of descriptive method which is a method of research that attempt to describe and interpret the objects in accordance with reality. Keywords: Jane Eyre, Plot, Theme, Setting, Character & Characterization, and Point of View.